Obesity, Dietary Patterns, and Cardiovascular Disease: A Narrative Review of Metabolic and Molecular Pathways - Cristina Dina; Delia Mirela Tit; Ada Radu; Gabriela Bungau; Andrei-Flavius Radu (Current Issues in Molecular Biology)
Cardiovascular diseases (CVDs) remain the leading global cause of death, with obesity acting as a significant contributing factor through mechanisms such as chronic inflammation, insulin resistance, and endothelial dysfunction. Molecular pathways at the interface of obesity, diet, and CVDs reveal how altered lipid metabolism, oxidative stress, and inflammatory signaling contribute to CVD progression. Despite advancements in treatment, effective management of CVDs, particularly in the context of obesity, remains a challenge. This review addresses the gap in understanding the relationship between obesity, nutritional status, and CVD progression, evaluating the impact of dietary interventions such as low-carb, Mediterranean, ketogenic, and Dietary Approaches to Stop Hypertension diets on cardiovascular health. Key findings indicate that adipokines, interleukins, and tumor necrosis factor alpha play significant roles in inflammatory responses and insulin resistance, further exacerbating cardiovascular dysfunction. Furthermore, optimized dietary strategies have been shown to modulate several molecular pathways, improving cardiovascular risk factors and enhancing metabolic health. This review underscores the significance of understanding molecular metabolic pathways in the intricate relationship between obesity, diet, and CVDs. It highlights the role of personalized nutrition and comprehensive dietary patterns in the management of CVDs and advocates for further research to optimize dietary strategies for sustained cardiovascular health.